2014
DOI: 10.1177/0003319714523112
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cardiotoxic Effects of Adjuvant Trastuzumab Treatment and Its Relation to Oxidative Stress

Abstract: Our aim was to evaluate the acute cardiac toxicity of adjuvant trastuzumab treatment and its possible relation to changes in oxidative stress. Electrocardiographic and echocardiographic tissue Doppler imaging (TDI) parameters, activity of antioxidant enzymes (superoxide dismutase; SOD), and products of oxidative stress (malondialdehyde; MDA) were analyzed in 30 patients with early-stage breast cancer who had adjuvant trastuzumab treatment. There was a significant prolongation of QT interval after trastuzumab t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Vemurafenib, a selective BRAF inhibitor, was also associated with an increased in QT interval in 7–10% of patients . Trastuzumab, a monoclonal antibody that binds to the extracellular domain of HER2, resulted in CV effects including QT prolongation . Accordingly, many of these drugs have warnings for acquired QT prolongation on their labels.…”
Section: Cardiotoxic Kinase Inhibitors: Clinical Observations and Pro...mentioning
confidence: 99%
“…Vemurafenib, a selective BRAF inhibitor, was also associated with an increased in QT interval in 7–10% of patients . Trastuzumab, a monoclonal antibody that binds to the extracellular domain of HER2, resulted in CV effects including QT prolongation . Accordingly, many of these drugs have warnings for acquired QT prolongation on their labels.…”
Section: Cardiotoxic Kinase Inhibitors: Clinical Observations and Pro...mentioning
confidence: 99%
“…Similarly, TZM also binds to HER-2 and increases proapoptotic Bcl-xS expression while it decreases antiapoptotic Bcl-xL expression (Grazette et al, 2004;Sadek et al, 2017). These result in overwhelming ROS production and reduced ROS scavenging activities with consequent profound inhibition of SOD, CAT, GST, and GPx activities, reduced GSH levels as well as increased MDA levels of TZM-treated tissues (Dirican et al, 2014). The fact that the referred cardiac oxidative stress enzyme activities were profoundly inhibited by the TZM treatment, our finding is, thus, in tandem with other earlier findings (Dirican et al, 2014;Teppo et al, 2017;Gorini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These result in overwhelming ROS production and reduced ROS scavenging activities with consequent profound inhibition of SOD, CAT, GST, and GPx activities, reduced GSH levels as well as increased MDA levels of TZM-treated tissues (Dirican et al, 2014). The fact that the referred cardiac oxidative stress enzyme activities were profoundly inhibited by the TZM treatment, our finding is, thus, in tandem with other earlier findings (Dirican et al, 2014;Teppo et al, 2017;Gorini et al, 2018). Also, the fact that VAL, LSP, ADP and their fixed-dose combinations profoundly improved the activities of oxidative stress marker enzymes in the treated rats strongly suggest the protective role of these antihypertensive agents in TZM-induced tissue oxidative stress mediated via reduced caspase-3 and caspase-9 production as well as increased antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that ROS is essential for the pathogenesis of cardiac remodeling, which may also exert an obvious effect in the progression from pathological remodeling to heart failure [26, 27]. For example, Dirican et al reported a negative relevant relation between MDA and LVEF [28]. Yokota et al found that the activation of SOD, catalase, and GSHIPx did not decrease in failing hearts, which indicated that oxidative stress in heart failure is mainly owing to the increase of prooxidant generation rather than to the reduction of antioxidant defenses [29].…”
Section: Discussionmentioning
confidence: 99%